Recuperación de la biomasa mediante la sucesión secundaria, Cordillera Central de los Andes, Colombia - Ignacio del Valle, Jorge (Universidad de Costa Rica, 2011)
Estimations on biomass recovery rates by secondary tropical forests are needed to understand the complex tropical succession, and their importance on CO2 capture, to offset the warming of the planet. We conducted the study in the Porce River Canyon between 550 and 1 700m.a.s.l. covering tropical and premontane moist belts. We established 33 temporary plots of 50mx20m in secondary forests, including fallows to succesional forests, and ranging between 3 and 36 years old; we measured the diameter at breast height (D) of all woody plants with D=5cm. In each one of these plots we established five 10mx10m subplots, in which we measured the diameter betweem 1cm=D < 5cm of all woody plants. We estimated the biomass of pastures by harvesting 54 plots of 2mx2m, and of shrubs in the fallows by harvesting the biomass in 18 plots of 5mx2m. We modeled Bav (above ground live biomass of woody plants) and Brg (coarse root biomass) as a function of succesional age (t) with the growth model of von Bertalanffy, using 247t/ha and 66t/ha as asymptote, respectively. Besides, we modeled the ratios brg/bav=f(D) and Brg/Bav=f(t). The model estimated that 87 years are required to recover the existing Bav of primary forests through secondary succession, and 217 years for the Brg of the primary forest. The maximum instantaneous growth rate of the Bav was 6.95 t/ha/yr at age 10. The maximum average growth rate of the Bav was 6.26 t/ha/yr at age 17. The weighted average of the absolute growth rate of the Bav reached 4.57t/ha/yr and the relative growth rate 10% annually. The ratio brg/bav decreases with increasing D. The ratio Brg/Bav initially increases very rapidly until age 5 (25%), then decreases to reach 25 years (18%) and increases afterwards until the ratio reaches the asymptote (26.7%).